Analysis of Challenges and Opportunities in Strengthening Village Development Innovation for Village Community Welfare - Kharisma (Journal of Community Service and Rural Development, 2024)
Self-reliance of a community group in the contemporary context is often associated with village development. The collective attitude of the community towards social change plays an important role in achieving self-reliance. Intervention programs created by the government can help change community behavior towards self-reliance. These programs require active participation from the community. Qualitative research shows that the government is implementing and improving strategies to provide good services to rural communities in Indonesia. The focus of development is always on village communities, as they have the potential to positively impact every village in Indonesia. As the community is the best partner in the development process, the government works together with them, especially the village community, to achieve common goals.